Urban forestry planning using remote sensing/GIS technique - Ismail, Mohd Hasmadi; Jusoff, Kamaruzaman (Universiti Putra Malaysia Press, 2004)
Urban forestry has become an important value, not only for the aesthetic but also their effectiveness in the environmental control and health. There is a potential to plan and develop urban forest landscape in Malaysian cities due to her richness in plant biodiversity. The advances in remote sensing technology and geographic information system (GIS) technique have provided an effective tool not just for monitoring the change of environment but also very useful for planning, managing and developing of urban forest landscaping. This study was undertaken to assess the capability of integrating remote sensing and GIS to provide information for urban forest potential sites surrounding Kuala Lumpur International Airport (KLIA) and its vicinity. Landsat TM imagery scene 126.58 (path/row) in the form of computer compatible tape (CCT) taken in May 1996 was digitally processed and analysed using a PC-based PCI EASIPACE software system version 6.2. Ancillary data such as topographical map, land use map and soil series map were used to support the satellite data.Integrating satellite data and GIS produced a map 'showing the potential site for urban forest landscaping at KLIA. Future studies should attempt to utilize airborne hyperspectral high-resolution data for more accurate mapping and landscape planning process.